Adjuvant Sufentanil Decreased the EC50 of Epidural Ropivacaine for Labor Analgesia in Healthy Term Pregnancy - Xiang B; Yang J; Lei X; Yu J (Dove Medical Press, 2021)
Bo Xiang,1 Jian Yang,2 Xiaofeng Lei,1 Jin Yu1 1Department of Anesthesiology, Chongqing Health Center for Women and Children, Chongqing, 401147, People’s Republic of China; 2Department of Anesthesiology, Chongqing Dongnan Hospital, Chongqing, 401336, People’s Republic of ChinaCorrespondence: Jin YuDepartment of Anesthesiology, Chongqing Health Center for Women and Children, No. 120, Longshan Road, Yubei District, Chongqing, 401147, People’s Republic of ChinaTel +86-18623117820Fax +86-23-63702844Email dodoes@qq.comJian YangDepartment of Anesthesiology, Chongqing Dongnan Hospital, No. 98, Tongjiang Ave, Nanan District, Chongqing, 401336, People’s Republic of ChinaTel/Fax +86-23-62905685Email charlalice@sina.comObjective: The optimal concentration of ropivacaine as epidural labor analgesia combined with sufentanil has not been established. This study aimed to determine the median effective concentration (EC50) of epidural ropivacaine for labor analgesia in healthy term pregnancy when co-administered with sufentanil as an adjuvant or alone.Patients and Methods: Sixty healthy parturients scheduled for epidural labor analgesia were enrolled in the study. They were divided into a saline group (Group C) and an epidural sufentanil (0.5 μg/mL) group (Group S). The initial concentration of ropivacaine was set at 0.125%, which was then varied by 0.01% using the up-and-down sequential allocation method. The hemodynamics were continuously monitored during delivery. A visual analog scale was used to evaluate the degree of pain. The Ramsay sedation score, duration of the labor stages, the onset of epidural analgesia, and adverse effects were recorded. Neonatal outcomes were evaluated using the Apgar scores and umbilical artery blood gas analysis.Results: The EC50 of ropivacaine was 0.085% (95% CI, 0.079– 0.090%) in Group S and 0.109% (95% CI, 0.105– 0.112%) in Group C. The EC95 of ropivacaine was 0.096% (95% CI, 0.090– 0.118%) in Group S, and 0.116% (95% CI, 0.113– 0.127%) in Group C. The difference between the groups was statistically significant (p < 0.001). The stable hemodynamics, satisfactory analgesia, and good neonatal outcomes were comparable in both groups (P > 0.05).Conclusion: The EC50 of ropivacaine was reduced by 22% when co-administered with sufentanil for epidural labor analgesia in primipara. (www.chictr.org.cn; registration number: ChiCTR2000039547).Keywords: median effective concentration, ropivacaine, sufentanil, labor analgesia